Implementation of Student Internship Program among Bachelor of Science in Office Administration (BSOA) Students - Romance, Janine; Juanillas, Mary France; Rebulado, Rose Ann; Federis, Melany (The Indonesian Institute of Science and Technology Research, 2025)
This study was conducted to assess the Implementation of Student Internship Program among BSOA Students, who had undergone on Student Internship Program (SIP) which was guided by answering the profile of respondents which includes the Personal Profile in terms of Section, Age, Sex., Civil Status and Socio-Economic profile in terms of Household Monthly Income, Gadgets owned, and Educational Materials used of the respondents. The study also assessed the Extent of Implementation (Pre-deployment, Deployment, Exit); Challenges encountered by BSOA Students on the Student Internship Program (Pre-deployment, Deployment, Exit). The respondents were the 114 BSOA students for the academic year 2023-2024. This study utilized the Quantitative Descriptive Research Method and Slovin’s formula, percentage technique, weighted mean, and rank order method as the statistical tools. The study revealed that most of the respondents are from Section A and majority of the respondents belonged to age bracket of 21-22 years old and mostly are dominated by female which are single, it also revealed that the Household Monthly income of the respondents belong to Php15, 000 and below; The gadgets owned by most of the respondents is cellphone and the educational materials they used is learning module; as to extent of implementation of SIP, findings revealed that along pre-deployment, deployment, and exit, all garnered a verbal interpretation of very high extent. In terms of challenges encountered, the respondents’ average weighted mean interprets as seldom encountered. The output of this study is the proposed recommendations to enhance the Implementation of the Students' Internship Program among BSOA students.